Evaluating the Immunomodulatory Effect of Indukantham Gritham: An Ayurvedic Perspective (International Journal of Ayurveda and Pharma Research, 2024)
The basic principles of Ayurveda rely on the concept that Sharira is composed of Tridoshas (three humors), Panchamahabhuthas (five elements), Sapthadhatus (seven tissues). Any imbalance among them causes Roga. Ayurveda aims at maintaining the health of Swastha and curing the Roga in unhealthy. Classical texts of Ayurveda have defined immunity as (Vyadhikshamatwa) i.e., the ability of the body to prevent as well as arrest the progression of a Roga. In biomedical science immunology is that branch which covers the study of all aspect of immune response in all organisms. Indukantham Gritham an Ayurvedic medicine is recognized for its role in promoting health and enhancing immune function. It is composed of ghee, which is known for its rejuvenative properties, and several herbs with documented health benefits. Present article light on the concept of evaluating the immunomodulatory effect of Indukantham Gritham.